Peningkatan Hasil Belajar Matematika Siswa Melalui Model Pembelajaran Missouri Mathematics Project (MMP) : (Studi Komparatif pada Siswa Kelas VIII SMP Negeri 1 Kotabaru Kabupaten Karawang) - Chandra Sagul Haratua; Intan Shofiyanti; Ahmad Prayogo; Parmianti Parmianti; Latifah Tazkiyatunnisa (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to evaluate the effectiveness of the Missouri Mathematics Project (MMP) Learning Model in improving mathematics learning outcomes for junior high school students. This study employs a comparative approach, comparing mathematics learning outcomes between students taught using MMP and those taught using conventional teaching models. Data were collected through hypothesis testing of mathematics learning outcomes for both groups. The data analysis results indicate a significant difference in mathematics learning outcomes between the two groups, with a significance value (sig.) smaller than the commonly used significance level. These findings suggest that the implementation of MMP effectively improves mathematics learning outcomes for junior high school students. The practical implications of these findings are discussed in the context of developing more effective and inclusive mathematics teaching strategies.